Evaluation of plantar fasciitis improvement after shock wave therapy in calcaneal spur patients by musculoskeletal ultrasonography - Soad Said El Molla (SpringerOpen, 2021)
Abstract Background Plantar fasciitis due to calcaneal spur is a common cause of heel pain and functional disability, and its management presents a huge challenge for clinicians which results sometimes in unpleasant clinical outcomes. The efficacy of extracorporeal shock wave therapy (ESWT) as an alternative therapeutic option to surgical management after failure of conservative treatment has been addressed. Our aim was to evaluate the efficacy of ESWT in the treatment of plantar fasciitis in calcaneal spur patients using ultrasonography. Results The mean plantar fascia (PF) thickness was statistically significantly higher in the calcaneal spur patient group (5.66 ± 1.14 mm) than in the healthy control group (2.40 ± 0.35 mm), (P = 0.001). Significant PF thickness reduction, visual analog scale (VAS), and Roles and Maudsley score (RMS) improvement were observed (P < 0.001) after 4 sessions of ESWT. Conclusion PF thickness increases significantly in calcaneal spur patients and responds to treatment. ESWT decreases the thickness of the PF and improves pain and function significantly.